Case Report: Curetting Osteoid Osteoma of the Spine Using Combined Video-assisted Thoracoscopic Surgery and Navigation - Campos, Wuilker Knoner (Springer-Verlag, 2012)
BACKGROUND: A spinal osteoid osteoma is a rare benign tumor. The usual treatment involves complete curettage including the nidus. In the thoracic spine, conventional open surgical treatment usually carries relatively high surgical risks because of the close anatomic relationship to the spinal cord, nerve roots, and thoracic vessels, and pulmonary complications and postoperative pain. CASE REPORT: We report the case of a 16-year-old girl with a symptomatic osteoid osteoma at the T9 level whose lesion was currettaged using video-assisted thoracoscopic surgery (VATS) guided by a navigation system (VATS-NAV). There were no complications and the patient had immediate relief of the characteristic pain after surgery and was asymptomatic at 5 months’ followup. LITERATURE REVIEW: Progressive advances in the technology of spinal surgery have evolved to offer greater safety and less morbidity for patients. The advent of minimally invasive surgery has expanded the indications for VATS for anterior spinal disorders. Spinal navigation systems have become useful tools allowing localization and excision of the nidus of osteoid osteomas with minimal bone resection and without radiation exposure. CLINICAL RELEVANCE: The VATS-NAV combination in our patient allowed accurate localization and guidance for complete excision of a spinal osteoid osteoma through a minimally invasive approach without compromising spinal stability.